Nosocomial Pneumonia Associated to PVL-Producing Staphylococcus aureus in Children in Benin - BABAMOUSSA, Lamine; AHOYO, Théodora A. (My University, 2013)
We determined the type of toxins produced by Staphylococcus aureus strains and the possible source of contamination during an outbreak of nosocomial pneumonia in a Paediatric service in Benin.Data of 37 patients admitted in themalnourished unitwhowere diagnosed with pneumonia according to WHO definition and with radiological evidence of a pulmonary infiltrate were collected within six weeks. Pneumonia was further confirmed by the identification of corresponding pneumonia-related S. aureus. Samples were also collected from hospital personnel, the environment, and the food fed to the patients. Pulsed field gel electrophoresis (PFGE) was used to compare the bacterial profile from different sources. Among the 37 patients admitted during this period, 17 developedpneumonia and 10were associatedwithS. aureus strains.Nine patients infectedwith S. aureus PVL-producing strains had underlying diseases and developed an acute multilobar pneumonia, which was fulminating and rapidly became fatal in all except the oldest child. Most of the isolates found on sick children were similar to those from special nutrients consumed by children and on the personnel at the hospital.The highly probable relationships between children contamination and isolate presence in the special nutrient underline the rapid and disastrous dissemination of some PVL-producing isolates in this paediatric unit
Keywords: Pneumonia; PVL-Producing Staphylococcus aureus; hospital; Benin